2009
DOI: 10.4314/ajfand.v8i4.19202
|View full text |Cite
|
Sign up to set email alerts
|

Effects of two commercial meat tenderizers on different cuts of goat\'s meat in Namibia

Abstract: Most meat consumed in Namibia is derived from poultry, cattle, sheep and pigs, despite the fact that majority of commercial and communal farmers in Namibia keep goats. Goat's meat is not available in the formal market or in the supermarkets in Namibia and is rarely used locally for domestic or commercial purposes due to ethical reasons, alleged poor taste, toughness and unpalatability. It is regarded by some to be for the poor sector of the community and for export only. Others consider goats as pets and a few… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 8 publications
0
5
0
2
Order By: Relevance
“…Many studies of marinated meat concluded that marinades containing pineapple juice had the greatest impact on meat tenderness and caused the most intense structural and textural alterations, although the attractiveness of the meat worsened [8,9]. Bromelain has been extensively studied by several authors as meat tenderizer for various animals such as steak, mutton, chicken, and pork [30,54,55]. Pineapple peel bromelain was an efficient softener for the steak, chicken, and squid [30].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies of marinated meat concluded that marinades containing pineapple juice had the greatest impact on meat tenderness and caused the most intense structural and textural alterations, although the attractiveness of the meat worsened [8,9]. Bromelain has been extensively studied by several authors as meat tenderizer for various animals such as steak, mutton, chicken, and pork [30,54,55]. Pineapple peel bromelain was an efficient softener for the steak, chicken, and squid [30].…”
Section: Discussionmentioning
confidence: 99%
“…The meat was marinated in sequence to promote protein hydration. The presence of the pineapple bromelain promotes hydrolysis of myofibril proteins, resulting in increased meat softening by the collagenolytic activity of the enzyme (Bille, 2009).…”
Section: Salty Preparationsmentioning
confidence: 99%
“…The sample B10 (10 mg/L bromelains) got the highest value of mean sensory score and found significantly different (p<0.05) from other samples at a 5% level of significance. The tenderizing effect of bromelain was due to the hydrolysis of muscle protein via fragmentation of the myosin heavy chain (Ketnawa &Rawdkuen, 2011 andBille &Taapopi, 2008). The heating process also affects the tenderization process.…”
Section: Optimization Of Bromelain Enzyme Concentrationmentioning
confidence: 99%